Les activités sportives « hybrides » comme réponse à l’accélération des rythmes de vie - Matthieu Quidu (Temporalités)
Nowadays, most people experience a generalized acceleration of the pace of life. This race against the clock, which tends to become chronic, seems to affect not only professional and family obligations but also the field of leisure activities. In a context of temporal shortage, where time becomes a commodity as rare as it is valuable, dedicating a part of one’s free time to unproductive activities can only be granted on condition that one can get a return on investment. What kind of sport activities could satisfy this condition, allowing its practitioners to get value not only for money but also for time? Using a case study, the practice of the Mixed Martial Arts, a synthetic fighting sport, by the students at the École Normale Supérieure de Lyon and former alumni of the Preparatory Classes where they learned how to manage temporal urgency, we stress that, for this population, these so-called “hybrid” sports provide a satisfactory answer to temporal scarcity by permitting a commitment judged to be efficient.